PRELIMINARY EVIDENCE OF LANDSCAPE-LEVEL STRUCTURE IN A POPULATION OF A PERENNIAL HERB, Cypella herbertii (IRIDACEAE) - Devoto, Mariano (2016)
We present preliminary evidence for the existence of a genetic landscape-level structuring that might be a consequence of depressed pollen flow across heavily grazed populations of Cypella herbertii